2018
DOI: 10.21833/ijaas.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Cultural factors influencing e-commerce usability in Saudi Arabia

Abstract: E-commerce is internet based business activity, such as online retail activity. In Saudi Arabia, e-commerce has not kept pace with the global growth of online shopping. In order to find the reasons for low participation in ecommerce, this study explored the influence of several cultural factors in Saudi Arabia related to age, gender, and computer proficiency. Hypotheses were developed for the demographic and cultural factors influencing the adoption of e-commerce in Saudi Arabia based on the literature review.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Individuals' expected possibility of using ecommerce decreases as the age increases. Similar results were obtained in the literature [36][37][38]. In a study in which the consumer behaviors of online shoppers in Bangladesh were examined, it was observed that most of the e-commerce users consisted of individuals under the age of 40 for reasons such as saving time, price flexibility and product range [39].…”
Section: Discussionsupporting
confidence: 82%
“…Individuals' expected possibility of using ecommerce decreases as the age increases. Similar results were obtained in the literature [36][37][38]. In a study in which the consumer behaviors of online shoppers in Bangladesh were examined, it was observed that most of the e-commerce users consisted of individuals under the age of 40 for reasons such as saving time, price flexibility and product range [39].…”
Section: Discussionsupporting
confidence: 82%
“…In the study, it was concluded that as the age of individuals increases, the likelihood of experiencing problems with online shopping decreases. In some studies, it has been concluded that the probability of online shopping decreases as the age of individuals increases (Bhatnagar, & Ghose, 2004;Alqahtani, Goodwin, & de Vries, 2018;Beneke, Scheffer, & Du, 2010;Alkan & Unver, 2021). Therefore, the findings in this study could be associated with this situation.…”
Section: Discussionmentioning
confidence: 99%
“…(c) Hidden CRM is a form of CRM that requires consistent guidance. There are still many shortcomings in this type [29]. We start with the development of human resources, innovation, and technology.…”
Section: Figure 2 Framework: the Process Of Startup Development Methodologymentioning
confidence: 99%